Strategic Capabilities and Muslim Entrepreneurial Behavior: The Mediating Role of Competitive Advantage on MSME Performance - Sari, Nurfadilah Sindika; Akbar, Muhammad; Iskandar, Rizkiani; Utami, Ayu Putri; Wulandari, Efriza Pahlevi (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2026)
This study examines the effects of product innovation, digital marketing, and Muslim entrepreneurial behavior on the performance of Sharia-based MSMEs, with competitive advantage serving as a mediating variable within the Resource-Based View (RBV) framework. A quantitative explanatory approach was employed using a census of 153 fashion-sector MSMEs. Data was collected through Likert-scale questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that product innovation and Muslim entrepreneurial behavior have a positive and significant effect on MSME performance, while digital marketing does not show a significant direct effect. Competitive advantage positively influences performance but only mediates the relationship between Muslim entrepreneurial behavior and performance; it does not mediate the effects of product innovation and digital marketing. These findings suggest that Muslim entrepreneurial behavior functions as an intangible strategic resource that builds Sharia-based reputational capital and enhances firm performance. This study extends the RBV framework within the Islamic economics context by highlighting the strategic role of Islamic values in shaping MSME capabilities and performance.